Celebrating Howard Watkins' 40th Birthday in Backyard - Watkins, Howard::::::::: (1987)
Peggy Sanders, Don Leet, Leslie Prusia, Vickie Leet; in back: Barbara Gaines, Darren Belk, Larry Tunison, Alex Vavoulis, Babs Eskin, Saul Eskin, ?, Sandy Iyall; seated: Ellen Waterman, Jim Waterman; far right: Cynthia Manzer, Dr. John Pickering; Greg Kamptner